2019
DOI: 10.1051/bioconf/20191203018
|View full text |Cite
|
Sign up to set email alerts
|

Structure, organization and a vision: Reasons for the success of wine cooperatives?

Abstract: Several studies have found that wine cooperatives struggle to produce high quality grapes allowing them to produce better quality wines and to receive higher retail prices. In contrast, cooperatives in South Tyrol perform well and receive price premiums for wine quality relative to privately-owned local competitors. We identify the structural, organizational and social factors (i.e., elements of social capital) that may contribute to the economic success of a cooperative enterprise, surveying individual member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The international literature has recently focussed on the competitiveness of wine systems, preferring to focus on smaller systems (usually regional) where a wine-producing "vocation" in this field is the exception when compared to national macro-systems (Rossi, 2013). Consequently, there exists copious references in the literature to the success of wine cooperatives, with authors having addressed this matter from several points of view (Schamel, 2019;Fanasch and Frick, 2018;Valette et al, 2018;Schimmenti et al, 2014). For example, various authors have focussed on the strategic process and the strategies used by cooperatives (Couderc and Marchini, 2011;Bono et al, 2012;Rossi, 2013) by making reference to comparative studies.…”
Section: Strategic Performance Of Wine Cooperativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The international literature has recently focussed on the competitiveness of wine systems, preferring to focus on smaller systems (usually regional) where a wine-producing "vocation" in this field is the exception when compared to national macro-systems (Rossi, 2013). Consequently, there exists copious references in the literature to the success of wine cooperatives, with authors having addressed this matter from several points of view (Schamel, 2019;Fanasch and Frick, 2018;Valette et al, 2018;Schimmenti et al, 2014). For example, various authors have focussed on the strategic process and the strategies used by cooperatives (Couderc and Marchini, 2011;Bono et al, 2012;Rossi, 2013) by making reference to comparative studies.…”
Section: Strategic Performance Of Wine Cooperativesmentioning
confidence: 99%
“…The coordination of quantities of grapes delivered by members to a given cooperative is a challenge for more traditional cooperatives. On the one hand, individual members can be motivated to oversupply their products to raise their revenues and on the other hand, this inevitably involves an increase in total market supply, leading to decreasing prices (Schamel, 2019). A recent empirical study (Cadot et al, 2016), focusing on 39 cooperatives in the Bordeaux wine region, demonstrated that members of traditional cooperatives prioritise their short-term income against the long-term survival of the organisation.…”
Section: Strategic Performance Of Wine Cooperativesmentioning
confidence: 99%
See 1 more Smart Citation
“…High grape pay-outs and member satisfaction can only be achieved if the cooperative is working successfully in the market and generating a surplus. Schamel [63] found that the success of wine cooperatives also depends on particular social factors (e.g. member commitment and trust) as well as on organizational control variables (e.g.…”
Section: Need For Market Orientation and Competitive Strategymentioning
confidence: 99%